PERMAINAN TRADISIONAL STIMULUS PENINGKATAN SOFT SKILL ANAK-ANAK KAMPUNG KEBAGUSAN - Sari, Martdian Ratna; Dina Nilam Rosalika; Nurul Fauziah; Mustika Asabi (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2024)
Formal education will make children smart on the academic side but not necessarily on the interpersonal side. Good interpersonal skills are very important in everyone's life. With good interpersonal skills, children are expected to have emotional intelligence, therefore, good interpersonal skills must be formed and trained consistently. This interpersonal ability cannot only be taught through classroom learning, but learning that provides direct experience is needed. The living environment has a very large influence on interpersonal development such as the environment in Kebagusan Village. Considering the environmental conditions of Kebagusan Village and based on the results of interviews and observations, the STM PPM PkM Team is committed to providing training to improve soft skills/interpersonal skills for Kebagusan Village children through traditional game stimuli. Based on the results of the evaluation of the implementation of soft skill training through traditional games, it shows changes in the behavior of children who are starting to dare to answer questions, dare to volunteer to be leaders in groups, dare to start conversations with the PKM STM PPM Team, show initiative when their friends experience difficulties, and start understand the meaning of mutual respect which is shown by being willing to listen when someone else is talking and not busy talking to himself. The conclusion from this community service activity is that the soft skills/interpersonal abilities of the children of Kebagusan Village are more honed if they are stimulated from an early age.